FANATISME PADA PERGURUAN CABANG OLAHRAGA KARATE DITINJAU DARI SOSIAL, BUDAYA DAN OLAHRAGA (STUDI KASUS PADA DOJO DI KABUPATEN JEPARA) (Universitas Negeri Semarang, 2020)
ABSTRACTIta Setiyawati. 2020. Fanaticism in the Karate Sports College in terms of Social, Culture, and Sports (Case Study of the Dojo in Jepara Regency). Thesis, Department of Physical Education, Health, and Recreation, Faculty of Sport Science, Universitas Negeri Semarang. Supervisor: Dr. Heny Setyawati, M.Si. Kata kunci: Fanaticism, Karate, Social, Culture, Sports. This research is motivated by the development of existing colleges in Jepara Regency resulting in increased competition between universities and fanatsime between universities is increasingly visible when in a match. Then there are five karate schools with one school, shotokan. Some universities in Jepara Regency include; Lemkari, Inkai, Inkanas, BKC, and Inkado. The problem in this research is how much the level of fanaticism in the karate sport branch (case study in Dojo in Jepara Regency) in terms of social, cultural and sports. The purpose of this research is to find out how much the level of fanaticism in karate sports is viewed from Culture, Social and Sports (Case Study of Dojo in Jepara Regency)